Petrogenesis and geochronology of Precambrian granitoid gneisses in Western Liaoning Province: Constraints on Neoarchean to early Paleoproterozoic crustal evolution of the North China Craton - Wang, W.; Liu, S.; Wilde, Simon; Li, Q.; Zhang, J.; Bai, X.; Yang, P.; Guo, R. (Elsevier BV, 2012)
The North Chaoyang-Fuxin-Yixian granite-greenstone belt (NCFY-GGB) at the northern margin of the Eastern Continental Block of the North China Craton is composed chiefly of metamorphic volcanic and volcano-sedimentary rocks and granitoid gneisses. The magmatic precursors of these granitoid gneisses are diorites, tonalites, trondhjemites, granodiorites and monzogranites. These granitoid gneisses can be divided into two groups: a high Mg group (HMG) and a low Mg group (LMG) according to their contrasting geochemical characteristics. Petrogenetic studies indicate that the HMG magmas were derived from partial melting of a subducted oceanic slab, which was contaminated by mantle peridotites during their ascent, whereas the LMG magmas were generated from the partial melting of lower continental crust composed chiefly of metamorphosed basaltic and pelitic rocks. LA-ICPMS zircon U–Pb dating reveals that granitoid gneisses in the HMG and low-K granitoid gneisses in the LMG were emplaced at 2511–2521 Ma, but that the high-K granitoid gneisses in the LMG formed later at ca. 2495 Ma. These Neoarchean to early Paleoproterozoic granitoid gneisses, intrusive into the metamorphic volcanic assemblages of the Yixian-Fuxin greenstone belt, indicate that the NCFY-GGB was developed at a Neoarchean to early Paleoproterozoic Andean-type active continental margin.